Rituximab in combination with chemotherapy for the treatment of chronic lymphocytic leukaemia in clinical practice. (22nd March 2018) - Reiser, Marcel; Dörfel, Steffen; Hensel, Manfred; Hoesl, Mark; Jordan, Wolf‐Oliver; Koenigsmann, Michael; Meyer, Dirk; Reichert, Dietmar; Schwarzer, Andreas; Marquardt, Moritz; Kellershohn, Kerstin; Jentsch‐Ullrich, Kathleen
Abstract: Objectives: This study was conducted to investigate the real‐world effectiveness and tolerability of rituximab‐containing chemoimmunotherapies, which have become the standard of care for chronic lymphocytic leukaemia (CLL), particularly for physically fit patients. Furthermore, current treatment patterns in clinical practice were documented, and an unselected real‐life population was compared with older, comorbid patients. Methods: Prospective, multicentre, observational study with rituximab‐containing chemoimmunotherapy in CLL patients. Results: Of 681 patients in total, 485 were enroled in cohort 1 (unselected) and 196 in cohort 2 (comorbid "slow‐go" patients). The median patient age was higher than in most randomised controlled trials (cohort 1: 70 years and cohort 2: 75 years). The most common treatment regimen in both first‐line and relapsed patients was rituximab‐bendamustine. Two‐year progression‐free survival rate for first‐line therapy was 84.1% for cohort 1 and 69.8% for cohort 2 (with best overall response rate 81.8% for cohort 1 and 76.6% for cohort 2). General and B‐symptoms declined during treatment and remained at low level or decreased further until study end. The safety profile observed in randomised clinical trials was confirmed. Conclusion: Chemoimmunotherapy with rituximab is feasible and safe in a wide variety of clinical settings in CLL, including the treatment of older patients with comorbidities (ClinicalTrials.gov NCT01178086).